Immunogenic inhibition of prominent ruminal bacteria as a means to reduce lipolysis and biohydrogenation activity in vitro. (1st March 2017) - Edwards, Holly D.; Shelver, Weilin L.; Choi, Seongho; Nisbet, David J.; Krueger, Nathan A.; Anderson, Robin C.; Smith, Stephen B.
Highlights: All antibodies were effective at reducing lipolysis. The anti- B. fibrisolvens showed a tendency for a reduction in biohydrogenation. Antibody against purified lipase was more effective than whole cell preparation. Antibodies displayed cross reactivity against other pure cultures. Saturation of fatty acids in ruminal animals can be immunologically inhibited. Abstract: Lipolysis and biohydrogenation in ruminal animals promote the accumulation of saturated fatty acids in their meat and milk. Antibodies were generated against key ruminal lipase contributors Anaerovibrio lipolyticus, Butyrivibrio fibrisolvens, Propionibacterium avidum and acnes. An anti- Pseudomonas lipase antibody was generated to determine if an antibody against a purified protein would be more effective. Each bacterium was cultured and assayed without or with increasing levels of each antibody. Butyrivibrio fibrisolvens H17C also participates in biohydrogenation and therefore the antibody was tested to determine if it could effectively reduce biohydrogenation . Butyrivibrio fibrisolvens was assayed without and with the anti- B. fibrisolvens antibody and linoleic or α-linolenic acid. All antibodies were effective at reducing lipolysis with the anti- Pseudomonas lipase averaging a 78% reduction. The anti- B. fibrisolvens showed a tendency for a reduction ( P  = 0.0713) in biohydrogenation products of α-linolenic acid. Results demonstrate that lipolysis and biohydrogenation can be immunologically inhibited in vitro .